A Microplane Model That Considers Dynamic Fatigue Damage and Its Applications in Concrete Infrastructure - Changjin Qin; Xiaogang Dong; Biao Wu; Lidong Cai; Shaohua Wang; Qing Xia (Infrastructures)
In significant infrastructure, it takes more than simple fatigue load capacity calibration to meet design and analysis requirements; more importantly, fatigue damage evolution and remaining life assessments should be undertaken. Therefore, this paper proposes a dynamic fatigue damage analysis method for concrete infrastructures based on an extended microplane model. This study extends the original microplane model to encompass steel fiber-reinforced concrete, fatigue, and dynamic analysis. In particular, the influence of the material rate-dependent effect (usually related to loading frequency) on the material’s properties is considered. The model’s validity is corroborated through benchmark tests and illustrative examples. Subsequently, the model is employed for the dynamic fatigue analysis of concrete members and concrete infrastructure, with a particular focus on the material rate-dependent effects and the influence of steel fiber on the fatigue behavior of concrete. It is demonstrated that incorporating steel fiber into concrete can markedly enhance its fatigue resistance, a phenomenon that can be reflected in the present model. Furthermore, accelerated fatigue experiments may overestimate the fatigue life of concrete materials. However, when conducting dynamic fatigue analysis of structures, incorporating rate-dependent materials may result in underestimating the fatigue damage experienced by concrete infrastructures. The model provides a helpful predictive tool for assessing progressive fatigue damage in concrete infrastructure under a complex range of loading scenarios, contributing to structural resilience and promoting sustainability.